The oncolytic virotherapy era in cancer management: prospects of applying H-1 parvovirus to treat blood and solid cancers - Angelova, Assia L.; Witzens-Harig, Mathias (Frontiers in oncology, 2017)
Non-Hodgkin lymphoma (NHL) and leukemia are among the most common cancers worldwide. While the treatment of NHL/leukemia of B-cell origin has much progressed with the introduction of targeted therapies, few treatment standards have been established for T-NHL/leukemia. As presentation in both B- and T-NHL/leukemia patients is often aggressive and as prognosis for relapsed disease is especially dismal, this cancer entity poses major challenges and requires innovative therapeutic approaches. In clinical trials, oncolytic viruses (OVs) have been used against refractory multiple myeloma (MM). In preclinical settings, a number of OVs have demonstrated a remarkable ability to suppress various types of hematological cancers. Most studies dealing with this approach have used MM or B- or myeloid-cell-derived malignancies as models. Only a few describe susceptibility of T-cell lymphoma/leukemia to OV infection and killing. The rat H-1 parvovirus (H-1PV) is an OV with considerable promise as a novel therapeutic agent against both solid tumors (pancreatic cancer and glioblastoma) and hematological malignancies. The present perspective article builds on previous reports of H-1PV-driven regression of Burkitt's lymphoma xenografts and on unpublished observations demonstrating effective killing by H-1PV of cells from CHOP-resistant diffuse large B-cell lymphoma, cutaneous T-cell lymphoma, and T-cell acute lymphoblastic leukemia. On the basis of these studies, H-1PV is proposed for use as an adjuvant to (chemo)therapeutic regimens. Furthermore, in the light of a recently completed first parvovirus clinical trial in glioblastoma patients, the advantages of H-1PV for systemic application are discussed.
Gesehen am 14.06.2018